2021
DOI: 10.1136/bmjresp-2021-000915
|View full text |Cite
|
Sign up to set email alerts
|

Air quality, Environment and Respiratory Outcomes in Bronchopulmonary Dysplasia, the AERO-BPD cohort study: design and adaptation during the SARS-CoV-2 pandemic

Abstract: IntroductionAlmost half of all school-age children with bronchopulmonary dysplasia (BPD) have asthma-like symptoms and more suffer from lung function deficits. While air pollution and indoor respiratory irritants are known to affect high-risk populations of children, few studies have objectively evaluated environmental contributions to long-term respiratory morbidity in this population. This study aimed to examine the role of indoor environmental exposures on respiratory morbidity in children with BPD.Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Multiple studies have demonstrated an association between increased asthma morbidity and indoor air pollution exposure [37][38][39], and more recently identified vulnerable populations to indoor air pollutants [38,39]. We recently [39] reported adverse respiratory health outcomes in children born prematurely, where indoor exposure to black carbon (BC) and PM 2.5 was associated with an increase in asthma symptom days and worsened lung function, respectively, stimulating additional research in this area [40]. Permaul et al [38] reported an increased risk in asthma symptom days with indoor NO 2 exposure for obese children.…”
Section: Indoor Exposuresmentioning
confidence: 99%
“…Multiple studies have demonstrated an association between increased asthma morbidity and indoor air pollution exposure [37][38][39], and more recently identified vulnerable populations to indoor air pollutants [38,39]. We recently [39] reported adverse respiratory health outcomes in children born prematurely, where indoor exposure to black carbon (BC) and PM 2.5 was associated with an increase in asthma symptom days and worsened lung function, respectively, stimulating additional research in this area [40]. Permaul et al [38] reported an increased risk in asthma symptom days with indoor NO 2 exposure for obese children.…”
Section: Indoor Exposuresmentioning
confidence: 99%